Shighah Mubalaghah dalam Penafsiran: Analisis Linguistik pada Pendekatan Thabari dan Qurthubi - Suhemi, Emi (El-Sunan: Journal of Hadith and Religious Studies, 2023)
This study explores the common method of interpreting the Quran using a linguistic approach, where a commentator's proficiency in the Arabic language, especially in the morphological aspect related to the material of shighah al-mubalaghah, becomes crucial. The aim of this study is to identify the extent to which the method of shighah al-mubalaghah is applied in interpretation, with a focus on the interpretations of Thabari and Qurthubi. This study adopts a library research and content analysis approach, utilizing qualitative descriptive analysis. The shighah al-mubalaghah method serves as a tool to analyze verses of the Quran found in the commentaries of Thabari and Al Qurthubi. The results indicate that both commentators actively employ the shighah al-mubalaghah method in interpreting Quranic verses. Thus, it can be concluded that shighah al-mubalaghah plays a significant role in guiding interpreters in interpreting Quranic verses in accordance with their contextual meanings. ABSTRAK Kajian ini mengeksplorasi metode umum penafsiran al-Qur’an dengan pendekatan linguistik, di mana kemampuan seorang mufassir dalam Bahasa Arab, terutama pada aspek morfologis yang berkaitan dengan materi shighah al-mubalaghah, menjadi krusial. Tujuan kajian ini adalah untuk mengidentifikasi sejauh mana kaedah shighah al-mubalaghah diterapkan dalam penafsiran, dengan fokus pada penafsiran Thabari dan Qurthubi. Kajian ini bersifat library research dan content analysis dengan menggunakan metode analisis deskriptif kualitatif. Kaedah shighah al-mubalaghah digunakan sebagai alat untuk menganalisis ayat-ayat al-Qur’an yang terdapat dalam kitab tafsir karya Thabari dan Al Qurthubi. Hasil penelitian menunjukkan bahwa kedua penafsir tersebut secara aktif menerapkan kaedah shighah al-mubalaghah dalam penafsiran ayat-ayat Al-Qur’an. Dengan demikian, dapat disimpulkan bahwa shighah al-mubalaghah memiliki peran yang signifikan dalam membimbing penafsir dalam menginterpretasikan ayat-ayat Al-Qur’an sesuai dengan konteksnya.